It's not evidence, it's insight: bringing patients' perspectives into health technology appraisal at NICE. Issue 1 (December 2016) - Staley, Kristina; Doherty, Caroline
Plain English summary Health technology appraisal involves reviewing the findings from clinical trials and economic data to produce guidance on how health technology should be used. This task is carried out by appraisal committees in NICE. One of the several ways in which patients can feed their views into these committees is via a written patient statement. We asked nine committee members about what difference the information from patients makes to their decision-making. The Committee members reported that written patient statements offer a different perspective when reviewing the clinical and economic data. This can have a profound impact when a committee draws conclusions based solely on the data, which may not reflect the reality of patients' lives. The patients' and carers' input provides meaning to the data, 'bringing the numbers to life'. It identifies if the technology has any wider impacts than what's been reported in the clinical trial, and also if the trial has measured what's important to patients. We conclude that the written patient statement adds value to the decision-making process by helping Committee members to make sense of the clinical and economic data-it makes them look at the evidence 'in a different light'. Patients' stories are very effective in this context, because they have the power to communicate and to challenge Committee members' assumptions. Understanding this difference between analysing research evidence and drawing on patients' insights is important in thinking about what's needed in a written patient statement and the best way to obtain it. Abstract Background Health technology appraisal involves reviewing clinical and economic data to inform guidance on the use of technology. In England this task is carried out by appraisal committees within the National Institute for Health and Care Excellence (NICE). Patients are not committee members as they have a vested interest in the outcome, but one of the several ways they are involved is through submitting a written patient statement, which is considered by the committee during its deliberations. We aimed to find out how the written patient statement adds value to the decision-making process by exploring how it is used in practice. Methods Semi-structured interviews were conducted with nine members of NICE appraisal committees. The interviews were transcribed and analysed thematically. We drew on published evidence of the impact of patient involvement on clinical research and our experience of supporting organisations to produce written patient statements to analyse the findings. Results Committee members reported that written patient statements offer a different perspective when evaluating clinical and economic data. This can have a profound impact when a committee draws conclusions based on data that may not reflect the reality of the patient experience. Information from patients and carers also provides context and meaning to the data, by explaining its real-life implications. It identifies wider impacts of a technology that may not have been assessed in a clinical trial, as well as commenting on whether what has been measured in a trial is relevant to patients. The main barrier to using the written patient statement is the misperception that it is a form of research 'evidence', when in fact it takes the form of experiential knowledge - or insight. Conclusions The written patient statement adds value by aiding Committee members in their interpretation of existing evidence – it enables them to consider this evidence 'in a different light'. In this context, patients' experiential knowledge is effective because it is subjective, emotional and anecdotal. It then has the power to communicate and to challenge assumptions based on the data alone. Understanding this difference between using evidence and insights has implications for the content of a written patient statement and the approaches used to obtain it.